Analisis Asuhan Keperawatan Bersihan Jalan Napas Tidak Efektif pada Tn. R dengan TB Paru Menggunakan Terapi Batuk Efektif di Ruang Lavender Atas RSUD Kardinah Kota Tegal - Indri Heri Susanti; Agun Pangestu (Jurnal Anestesi, 2024)
Tuberculosis (TB) Lung is an infectious disease caused by the bacterium Mycobacterium tuberculosis. There are several species of Mycobacterium, including: M. tuberculosis, M. africanum, M. bovis, M. leprae etc. Which is also known as Acid Resistant Bacteria (BTA). This study aims to determine the involvement of care in pulmonary TB patients with ineffective airway hygiene problems in the Upper Lavnder Room at Kardinah Hospital, Tegal. The research design is a descriptive case study through a case study of pulmonary TB patients with ineffective airway hygiene problems in the Upper Lavnder Room at Kardinah Hospital, Tegal. Researchers in collecting data through the stages of anamnesis, observation, physical assessment, and documentation. The results of this study show that problems that occur with clients can be resolved on the 3rd day which is marked by a decrease in shortness of breath. In conclusion, the problem of complications can be resolved on the 3rd day with actions including monitoring breathing patterns, placing a semi-fowler or fowler and prohibiting effective coughing techniques.